2009
DOI: 10.1007/s11250-009-9449-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological change in camel milk composition (Camelus dromedarius) 1. Effect of lactation stage

Abstract: The change in the composition of camel milk in four dromedaries was studied by including the common measured parameters: protein, total fat, lactose, main minerals (calcium, phosphorus, and iron), and vitamin C. The fat matter varied from 4.34% to 7.81% with a slight decrease all along the lactation and a minimal value at the 14th week corresponding to the lactation peak. Those variations were less important for protein content (from 2.58% to 3.64%), but the minimal value was observed at the 14th week also. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
12
16
0
Order By: Relevance
“…The variation in mineral reflects many genetic and environmental factors such as the system of feeding and browsing of different plants. The mean content of fat and protein in our study shows a lower results compared to those reported by Konuspayeva et al (2009b), Igbal et al (2001) and Zeleke (2007), but otherwise close to results reported by Farah and Fisher (2004). This wide variation in the milk constituents is generally attributed to some factors such as breed, herd management, sampling technique used and feed quality (Al-Shaikh and Salah, 1994).…”
Section: Milk Compositionsupporting
confidence: 74%
“…The variation in mineral reflects many genetic and environmental factors such as the system of feeding and browsing of different plants. The mean content of fat and protein in our study shows a lower results compared to those reported by Konuspayeva et al (2009b), Igbal et al (2001) and Zeleke (2007), but otherwise close to results reported by Farah and Fisher (2004). This wide variation in the milk constituents is generally attributed to some factors such as breed, herd management, sampling technique used and feed quality (Al-Shaikh and Salah, 1994).…”
Section: Milk Compositionsupporting
confidence: 74%
“…These results are in consonance with the results of Wernery et al [35]. The fat content in the present study was found lower in comparison to that of fat content noted in camels by [5,18,23,26,28,29,31,32,36,37]. This low percentage is certainly due to an environmental difference reflecting the desert nature of our country.…”
Section: Basic Composition Of Camel Milksupporting
confidence: 91%
“…These results are in consonance with the results of [11,17,25,26]. These findings are higher compared to those of [26][27][28][29][30][31] which revealed the protein content of camel milk ranging from 1.80-3.9%. While the protein content in the present study were lower than those reported by [32,33] (5.78 and 5.5%, respectively).…”
Section: Basic Composition Of Camel Milksupporting
confidence: 88%
See 1 more Smart Citation
“…This could due to difference in feed intake by the camel and to difference in breeds, geographic locality, lactating stage and the environment. [5], [19] determined the fatty acid composition and cholesterol content in camel's milk of Bactrian, dromedary and hybrids from different regions of Kazakhstan, and in different seasons. Great differences in fatty acid composition occurred between regions.…”
Section: Resultsmentioning
confidence: 99%